Superior electrochemical performances of LaMgNi alloys with A2B7/A5B19 double phase. (15th March 2019) - Fan, Yanping; Zhang, Lu; Xue, Chunjian; Fan, Guangxin; Liu, Jingjing; Liu, Baozhong; Han, Shumin
Abstract: Here, phase transformation and electrochemical characteristics of non-stoichiometry La4 MgNi x ( x  = 16, 17 and 18) hydrogen storage alloys were studied. It is found that after annealed at 1223 K for 24 h, the minor AB3 and AB5 phases in La4 MgNi16 alloy transform into A2 B7 phase by a peritectic reaction and the La4 MgNi16 alloy shows a A2 B7 single phase structure. Double phase structures of A2 B7 /A5 B19 are obtained in La4 MgNi17 and La4 MgNi18 alloys after annealed at the same condition. The abundance of A5 B19 phase increases as x increases, indicating the increasing x value contributes to the formation of A5 B19 phases. Electrochemical studies show that the maximum discharge capacity and capacity retention at the 100 th charge/discharge cycles ( S 100 ) of A2 B7 single phase La4 MgNi16 alloy is 373 mAh g −1 and 78.4%, respectively. The appearance of A5 B19 (minor) phase in the La4 MgNi17 alloy makes a remarkable improvement in the discharge capacity from 373 mAh g −1 to 388.8 mAh g −1, as well as the S 100 from 78.4% to 90.1%. It is believed that the LaMgNi-based alloy with the A2 B7 (main)/A5 B19 (minor) phase structure possesses the good overall electrochemical properties and is applicable to the high-power and long-cycle life negative electrode material for nickel metal hydride batteries. Highlights: Increasing x value contributes to the formation of A5 B19 phase. Annealing improves the C max and reduces the HRD. The cycling stability of La4 MgNi17 alloy reaches 90.1% at the 100 th cycle. Alloy with A2 B7 (main)/A5 B19 (minor) phase possesses outstanding performances.